Exploring the Meteorological Impacts of Surface and Rooftop Heat Mitigation Strategies Over a Tropical City. Issue 8 (15th April 2023) - Khan, Ansar; Khorat, Samiran; Doan, Quang‐Van; Khatun, Rupali; Das, Debashish; Hamdi, Rafiq; Carlosena, Laura; Santamouris, Mattheos; Georgescu, Matei; Niyogi, Dev
Abstract: Different heat mitigation technologies have been developed to improve the thermal environment in cities. However, the regional impacts of such technologies, especially in the context of a tropical city, remain unclear. The deployment of heat mitigation technologies at city‐scale can change the radiation balance, advective flow, and energy balance between urban areas and the overlying atmosphere. We used the mesoscale Weather Research and Forecasting model coupled with a physically based single‐layer urban canopy model to assess the impacts of five different heat mitigation technologies on surface energy balance, standard surface meteorological fields, and planetary boundary layer (PBL) dynamics for premonsoon typical hot summer days over a tropical coastal city in the month of April in 2018, 2019, and 2020. Results indicate that the regional impacts of cool materials (CMs), super‐cool broadband radiative coolers, green roofs (GRs), vegetation fraction change, and a combination of CMs and GRs (i.e., "Cool city (CC)") on the lower atmosphere are different at diurnal scale. Results showed that super‐cool materials have the maximum potential of ambient temperature reduction of 1.6°C during peak hour (14:00 LT) compared to other technologies in the study. During the daytime hours, the PBL height was considerably lower than the reference scenario with no implementation of strategies by 700 m for super‐cool materials and 500 m for both CMs and CC cases; however, the green roofing system underwent nominal changes over the urban area. During the nighttime hours, the PBL height increased by CMs and the CC strategies compared to the reference scenario, but minimal changes were evident for super‐cool materials. The changes of temperature on the vertical profile of the heat mitigation implemented city reveal a stable PBL over the urban domain and a reduction of the vertical mixing associated with a pollution dome. This would lead to crossover phenomena above the PBL due to the decrease in vertical wind speed. Therefore, assessing the coupled regional impact of urban heat mitigation over the lower atmosphere at city‐scale is urgent for sustainable urban planning. Plain Language Summary: In this research we evaluated the impact on the city meteorology and on the lower atmosphere due to the use of several heat mitigation technologies. The numerical simulations were carried out during typical summer hot days over an Indian tropical city. The heat mitigation strategies considered include very reflective materials (cool materials (CMs), super‐cool broadband radiative coolers) green roofs (GRs), changes in the vegetation fraction, and a combination of CMs and GRs (i.e., cool city (CC)). In particular, these mitigation strategies and technologies were incorporated in a weather model (the mesoscale weather research and forecasting coupled with a single‐layer urban canopy model) at the city‐scale. Our results showed that surface and rooftop heat mitigation strategies modify the meteorological fields and the dynamics of the lower atmosphere within the city during the hot summer days. The super‐cool broadband radiative coolers are most proficient in decreasing ambient temperature and planetary boundary layer, followed by CMs, CC, GRs, and augmenting vegetation fraction. The super‐cool broadband radiative coolers produced the most efficient strategy. Nevertheless, it has unintended consequences as they modify the temperature vertical profile, enhancing the stability over the urban domain and reducing the air's vertical mixing. The results presented show that the used model can be a valuable instrument to evaluate the implementation effects of heat mitigation technologies in the urban environment for extreme urban heat management, such as the newly developed super‐cool materials. However, careful attention should be paid to unintended consequences. Key Points: weather research and forecasting model is a valuable tool to evaluate the effects of heat mitigation measures in the urban environment for urban heat management Surface standard meteorological fields and lower atmospheric dynamics within the city are modified by heat mitigation measures The super‐cool broadband radiative coolers yielded the most efficient strategy for urban cooling in tropical context